Who Elected the Bankers? : Surveillance and Control in the World Economy - Pauly, Louis W. (Cornell studies in political economy., 2018)
A former banker and staff member of the International Monetary Fund, Louis W. Pauly explains why people are deeply concerned about the emergence of a global economy and the increasingly integrated capital markets at its heart. In nations as diverse as France, Canada, Russia, and Mexico, the lives of citizens are disrupted when national policy falls out of line with the expectations of international financiers. Such dilemmas, ever more conspicuous around the world, arise from the disjuncture between a rapidly changing international economic system and a political order still constituted by sovereign states. The evolution of global capital markets inspires an understandable fear among people that the governing authorities accountable to them are losing the power to make substantive decisions affecting their own material prospects and those of their children. Pauly points out that today's capital markets resulted from decisions taken over many years by sovereign states, and particularly by the leading industrial democracies, who simultaneously crafted the instrument of multilateral economic surveillance. The effort to build adequate political foundations for global capital markets spans the twentieth century and links the histories of such institutions as the League of Nations, the International Monetary Fund, the European Union, and the Group of Seven.